Adjuvant quercetin therapy for combined treatment of epilepsy and comorbid depression. (March 2017) - Singh, Tanveer; Kaur, Taranjot; Goel, Rajesh Kumar
Abstract: Epilepsy is one of the major neurological disorders frequently associated with psychiatric disorders such as depression. The predisposition of tryptophan metabolism towards kynurenine pathway has been reported as one of the plausible reasons for association of depression in epilepsy. Hence, this study was envisaged to evaluate the dose dependent inhibition of indoleamine 2, 3-dioxygenase (IDO) enzyme employing quercetin (screened employing in vitro method) with levetiracetam for combined management of epilepsy and comorbid depression. Kindling was induced in male swiss albino mice by administration of pentylenetetrazole subconvulsive doses (35 mg/kg, i.p.) at an interval of 48 ± 2 h. Kindled animals were treated with vehicle, levetiracetam (40 mg/kg/day i.p.) levetiracetam in combination with different doses of quercetin (10 mg/kg; 20 mg/kg; 40 mg/kg)/day/p.o. for 15 days. Except naïve, all the groups were challenged with pentylenetetrazole (35 mg/kg i.p.) on day 5, 10, and 15 to evaluate the seizure severity score. Depression was evaluated in all experimental groups using the tail suspension and sucrose preference test on days 1, 5, 10 and 15, 2 h after pentylenetetrazole challenge. Results suggested that vehicle treated kindled animals were significantly associated with depression. Chronic levetiracetam treatment significantly reduced seizure severity score, but further worsened the associated depression. Quercetin supplementation with levetiracetam dose dependently ameliorated depression associated with epilepsy. Neurochemical and biochemical findings also supported the behavioural findings of the study. Thus, our results suggested that supplementation of quercetin with levetiracetam could be explored further for combined treatment of epilepsy and comorbid depression. Graphical abstract: Highlights: The study explored the adjuvant role of quercetin with levetiracetam for combined treatment of epilepsy and depression. Neurochemical changes suggested altered tryptophan metabolism to be responsible for depression associated with epilepsy. Levetiracetam treatment decreased seizure severity and further worsened the comorbid depression. Adjuvant quercetin supplementation restored normal tryptophan and ameliorated comorbid depression. Quercetin supplementation with levetiracetam seems effective approach for combined management of epilepsy and depression.